INSAT-3D cloud microphysical product: retrieval and validation. Issue 4 (16th February 2019) - John, Jinya; Dey, Ipshita; Pushpakar, Anurag; Sathiyamoorthy, V.; Shukla, Bipasha Paul
ABSTRACT: The 6-channel Imager onboard the Indian geostationary satellite Indian National Satellite-3D (INSAT-3D) provides half-hourly multispectral images over the Indian monsoon region. The availability of shortwave infrared (SWIR) (1.6 μm) channel along with visible (0.6 μm) channel observations provide an opportunity to estimate cloud microphysical parameters (CMP) over the India and surrounding regions with high temporal frequency. In this paper, we describe the retrieval and validation of two important CMPs, i.e. cloud optical thickness (COT) and cloud effective radius (CER) over the ocean from INSAT-3D. This is the first time; a CMP product has been made available for INSAT-3D. We describe here the development of the forward model, based on a look-up-table (LUT) approach using Radiative transfer simulations. The inversion is carried out by selecting the vector (CMP) which provides the best match between the observed and simulated radiances. The present retrieval is limited to water clouds over ocean only. The retrieved INSAT-3D CMP were then compared with MODerate Resolution Imaging Spectroradiometer (MODIS) product for the months of January and July 2016. For cloudy month (July), the mean correlation between INSAT-3D and MODIS was 0.73 and 0.47 for COT and CER, respectively. Similarly, for the month of January with less cloud cover, the mean correlation was 0.60 and 0.40 for COT and CER, respectively. INSAT-3D products are available every half hourly in real time through web portal www.mosdac.gov.in and will be valuable for studying short-term variation in cloud-microphysics over the equatorial Indian Ocean.